INVENTARISASI EMISI SUMBER BERGERAK DARI TRANSPORTASI LAUT (NON-ROAD) DI WILAYAH PESISIR KOTA DENPASAR - Risky V.A, Desak Putu; Arthana, I Wayan; Suyasa, I Wayan Budiarsa (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 9 No 1 (2015)DO - 10.24843/EJES.2015.v09.i01.p02, 2015)
The development of marine transportation in Denpasar City followed by increasing number of visiting tourists who came to Denpasar City. This situation will contribute to air pollution problems. The purpose of this study was to determine the emission load produced by sea transportation in Denpasar City and the distribution of emissions gases such as NOx, SOx, HC, PM10, CO and CO2.Emission load calculations based on the guidelines of the EMEP Corinair Guidebook using Tier 3, which the emission factors used refer to the CORINAIR GB 2013 1.A.3.d. The results showed a total emission load from non-road mobile sources of marine transportation in the Denpasar city such as NOx is 14,583.69 tons/year, SOx by 85.49 tons/year, HC by 746.05 tons/year, PM10 at 503.53 tons/year, CO at 123,123.58 tons/year, and CO2 of 1,457,909.95 tons/year. Distribution of the source of pollutants mapped using GIS (Geographic Information System) shows that the emission load of NOx, SOx, HC and PM10 are likely identical, which mostly distributed around Benoa Port, but CO2 and CO have different patterns . The pattern of distribution of NOx, SOx, HC, and PM10 with the highest intensity follows the contours of the ships from Benoa Port. CO gas distribution pattern follows the contours of the ship from the Serangan Port and Sanur Port, CO2 gas distribution pattern almost evenly in almost all flow well from the Serangan Port, Sanur Port and Benoa Port
Keywords: Denpasar City, Emission Load, Benoa Port, Sanur Port, Serangan Port, Air Pollution